Knowledge and Awareness on Prevention of Sexually Transmitted Diseases among Commercial Sex Workers (TAJ: Journal of Teachers Association, 2018)
Objective: The main objective of the study was to assess the level of awareness on prevention and control of sexually transmitted diseases among 120 sex workers.Material and Methods: The cross-sectional study was conducted for one year. Data were collected through face to face interview using Bengali questionnaire. Data analysis was done using SPSS 17.0 software.Place and Period of Study: The study was conducted from January 1st to December 31st of 2014 among 120 sex workersliving in brothel of Daulodia,Rajbariin Bangladesh.Results: More than half (58.7%) of the respondents had children in the brothels. All the respondents (100%) heard about the sexually transmitted diseases. Majority (86.7%) of the respondents had knowledge on AIDS. Only a few (4.2%) respondents had knowledge on AIDS and Gonorrhea. Majority (91.7 %) of the respondents had knowledge on STD transmission from pregnant women. Almost all (97.5%, 98.3%)) of the respondents had the knowledge about STD transmissionnot from toilet or shaking hands respectively.Almost all of the (95.8%, 94.2%, 94.2%, 85.8% )respondents had the knowledge on STD transmission through sexual intercourse,injection,through mosquito,sharing same razor respectively. Most of them (81.7%) had good level of knowledge on STD transmission. Only above one tenth (11.7%) had moderate and poor level of knowledge.Almost all of them (96.7%, 95.9%, 95.9%) were found touse condom, agreed to keep one partner at a time,to reduce the number of sex partner respectively.Most of them (89.3%)did not knowthe HIV status of partner before sex,almost all (97.5%, 94.2% and 97.5%) agreed to avoid risky sex,to screen blood during transfusion, to avoid sharing needles & blade respectively. All (100%)of the respondents agreed for need of sexuality education for preventing STD.Almost all (98.30%)of the respondents had good awareness on Prevention and Control of Sexually Transmitted Diseases. There was no association between level of education and level of awareness (P> 0.005), between age and level of awareness (P> 0.005) and between duration of work and level of awareness (P> 0.005).Conclusion: Education is the most consistent and important determinant for prevention of STDs among all classes of people.TAJ 2016; 29(2): 47-56